Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kualitas Pelayanan Pada Dinas Sosial Kabupaten Bandung Barat - Susan Susanti; Nunung Sanusi; Fadli Agus Triansyah (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
This study aims to determine the effect of the work environment and work discipline on the quality of service at the West Bandung District Social Service. The method used in this study is a descriptive and quantitative method, with the survey method. The sample in this study was 50 employee respondents at the West Bandung Social Service. Sampling using population techniques. Data analysis techniques used statistical analysis with multiple regression models to answer the research hypothesis. The r study results show that the work environment and discipline significantly affect the quality of service at the West Bandung District Social Service. Based on the performance achievements at the West Bandung Regency Social Service in the year that the authors obtained through observation and research, the authors found a discrepancy between performance achievements and the level of community satisfaction based on the quality of service provided to the community. The author tries to dig deeper by conducting this research based on these findings. From the results of this study, the work environment and discipline positively affect the quality of service at the West Bandung Regency social service. Maintained properly by the Department so that employees feel at home and comfortable carrying out their work activities. In addition, work discipline must always be improved by complying with all the rules in the Office so that discipline can continue to be upheld. Because if the work environment and good work discipline will improve the quality of services provided to the community.